Politeness Maxims as A Positive and Negative Speech Act by The Characters “Habibie & Ainun” (2012) - Irma Nuraeni Salsabila; Vika Fransica (Syntax Corporation Indonesia, 2022)
A language is a tool for communicating in social life between individuals. Language makes people interact with each other. While the maxims is an important aspect of language so that the delivery and acceptance run well without causing problems in the future. This research uses a qualitative approach method with the analysis method, to conduct an in-depth analysis related to the findings of data from the film